Ammonia-sensitive material based on covalent organic framework as well as preparation method and application of ammonia-sensitive material

By modifying the transition metal on the covalent organic frame, metallized modified ammonia-sensitive materials are prepared, which solves the problems of poor adjustability and low sensitivity of the existing ammonia detection devices, and achieves high sensitivity, rapid response and excellent Repeat stability provides a high-performance solution for ammonia detection.

CN119306906AActive Publication Date: 2025-01-14SUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411604464.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing ammonia detection devices have problems such as poor adjustability, high operating temperature, narrow NH3 concentration range and low sensitivity.

Method used

By synthesizing the activated product H2-TPCOF and modifying different transition metals on a covalent organic framework using the coordination reaction principle, metallized modified M-TPCOF ammonia-sensitive material was prepared for use in quartz crystal microbalances to achieve high sensitivity and super High selectivity and fast response NH3 sensing.

Benefits of technology

Achieve high sensitivity, fast response and excellent repeatability to ammonia. The Co-TPCOF-modified ammonia detection device shows the highest response, fastest response/recovery time and ultra-high selectivity for high performance Ammonia detection provides new materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306906A_ABST
    Figure CN119306906A_ABST
Patent Text Reader

Abstract

The invention relates to an ammonia-sensitive material based on a covalent organic framework as well as a preparation method and application of the ammonia-sensitive material. Transition metal or hydrogen is modified on a covalent organic framework to obtain a metallized or hydrogen modified ammonia-sensitive material based on the covalent organic framework, the ammonia-sensitive material is prepared into an ammonia gas detection device, NH3 sensing with high sensitivity, high selectivity and quick response can be realized, and the ammonia gas detection device has excellent repeatability and stability and can be applied to the field of ammonia gas detection. And a new material is provided for the design of a high-performance ammonia gas detection device in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of gas detection technology, and in particular to ammonia-sensitive materials based on covalent organic frameworks, and preparation methods and applications thereof. Background Art

[0002] Ammonia, a colorless, odorless gas with a pungent odor, is widely used in the fields of chemical industry, light industry, fertilizer, pharmaceuticals, synthetic fibers, etc., and can be used as a biofuel to provide energy. When ammonia is emitted into the air, it will form PM2.5 particles with nitrogen compounds (NOx) and sulfides (SOx), causing serious air pollution. In addition, ammonia is not only corrosive and irritating to human skin and mucous membranes, but also denatures tissue proteins and destroys cells. When a certain amount of ammonia is inhaled by the human body, it will induce symptoms of poisoning, and in severe cases, it will cause blindness, and even more fatal. Therefore, from the perspective of people's livelihood health and environmental protection, real-time monitoring of ammonia is very necessary.

[0003] At present, the main methods for measuring the ammonia content in the air include optical method, calorimetry, gas chromatography and acoustic method. These methods require special instruments and equipment, and have problems such as high cost, large size, inconvenience in use, inability to monitor in real time, and difficulty in widespread promotion and application. In recent years, the rapid development of gas sensors can effectively overcome the problems of the above traditional methods and is a very promising ammonia detection method. Ammonia sensors are mainly divided into semiconductor sensors, electrochemical sensors, optical sensors and mass sensors. Among them, the quartz crystal microbalance (QCM) gas sensor is a typical mass gas sensor. It is based on the sensitivity of piezoelectric quartz wafer to mass. The sensitive film material modified on the surface of the quartz crystal wafer captures the gas to be measured, and the detection of the gas to be measured is achieved by measuring the change in the frequency of the quartz crystal. Compared with other gas sensors, sensors based on QCM have the advantages of low cost, high sensitivity, fast response time, good selectivity and can be used at room temperature. Therefore, they have received widespread attention from researchers in recent years and have been applied to many fields. However, the key to the development of QCM ammonia sensors lies in the development of ammonia-sensitive materials with excellent performance.

[0004] At present, a variety of materials have been used to prepare QCM ammonia sensors, including metal oxides, polymers, composite materials, etc. Metal oxides include TiO2, ZnO2, SnO2 and Fe3O4. Commonly used polymers are polyaniline (PANI), polyvinyl acetate (PVAc) and polyacrylonitrile (PAN), etc. They are all conductive polymers with excellent chemical stability and gas sensitivity. Common composite materials include the compounding of oxides and polymers, or the compounding of porous carbon materials and polymers. Although these materials have their own advantages, they also face some disadvantages, such as complex preparation process, low structural adjustability, poor selectivity, low repeatability, high operating temperature and poor chemical stability, so there is a need to further develop new ammonia-sensitive materials.

[0005] Covalent organic framework materials (COFs) are a new type of porous crystalline materials. Due to their low density, high stability, and tunable pore structure, they have potential applications in many fields such as sensing, catalysis, and energy storage. However, COF materials are currently commonly used in fluorescent sensors and electrochemical gas sensors. The research on mass-type gas sensors is still in its infancy and there are still challenges. Since COF structures often have dense stacking or interlacing, the utilization rate of active sites is low or the mass transfer is slow, resulting in the failure to fully develop their performance. Therefore, it is necessary to design and synthesize COF materials with different special morphologies to fully expose active sites and improve their performance for wide application. Therefore, it is urgent to use COF materials to design an ammonia-sensitive material to achieve specific detection of ammonia. Summary of the invention

[0006] To this end, the technical problem to be solved by the present invention is to overcome the problems of poor adjustability, high operating temperature, narrow NH3 concentration response range and low sensitivity of the ammonia detection device in the prior art.

[0007] In order to solve the above technical problems, the present invention uses 5,10,15,20-tetrakis (4-aminophenyl) porphyrin (TAPP) and 2,6-diformylpyridine (PCBA) to synthesize an activated product (H2-TPCOF), and uses the coordination reaction principle to modify different transition metals on the covalent organic framework by forming a coordination bond between the nitrogen atom on the pyrrole ring in the porphyrin molecule and the metal ion, thereby obtaining a metallized modified M-TPCOF (M = Co, Cu, Ni or Ag) ammonia-sensitive material, and prepares these ammonia-sensitive materials into an ammonia detection device, which can achieve high sensitivity, ultra-high selectivity and fast response NH3 sensing, and has excellent repetitive stability. The ammonia-sensitive materials modified with different transition metals show different detection performances under the same test conditions, indicating that different metal centers in the material have different binding characteristics with NH3 gas molecules. It is worth noting that the Co-TPCOF-modified ammonia detection device showed the highest response (155 Hz), the fastest response / recovery time (61s / 90s), ultra-high selectivity and excellent reusability for NH3 sensing, providing new materials for the design of high-performance ammonia detection devices in the future.

[0008] The first object of the present invention is an ammonia-sensitive material having the following general structural formula:

[0009]

[0010] Wherein M is a transition metal element or hydrogen.

[0011] Furthermore, the transition metal element is selected from one or more of cobalt, copper, nickel and silver.

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned ammonia-sensitive material in which M is hydrogen, wherein a porphyrin derivative is reacted with pyridine-2,6-dicarboxaldehyde in the presence of an organic solvent, and then the reaction is performed by freezing and degassing in a liquid N2 bath, followed by heating, and then washing to obtain the ammonia-sensitive material in which M is hydrogen.

[0013] The third object of the present invention is to provide a method for preparing the above-mentioned ammonia-sensitive material wherein M is a transition metal element, comprising the following steps:

[0014] S1, reacting a porphyrin derivative with pyridine-2,6-dicarbaldehyde in the presence of an organic solvent to prepare an ammonia-sensitive material in which M is hydrogen;

[0015] S2. Mixing an acetate solution containing a transition metal element with the ammonia-sensitive material in which M is hydrogen to obtain the ammonia-sensitive material in which M is a transition metal element.

[0016] Furthermore, the porphyrin derivative includes 5,10,15,20-tetrakis(4-aminophenyl)porphyrin.

[0017] Furthermore, the organic solvent is a mixed solution of a solvent and a catalyst.

[0018] Furthermore, the solvent is selected from one or more of ethanol, o-dichlorobenzene, butanol, toluene, and dioxane; and the catalyst is selected from one or more of acetic acid and scandium trifluoromethanesulfonate.

[0019] Furthermore, the reaction in step S2 is carried out under an inert atmosphere, the reaction temperature is 30-60° C., and the reaction time is 12-36 hours.

[0020] The fourth object of the present invention is to provide an ammonia detection device, comprising the above-mentioned ammonia-sensitive material or the ammonia-sensitive material prepared by the above-mentioned preparation method.

[0021] Furthermore, the ammonia detection device is implemented by a quartz crystal microbalance, which includes a quartz wafer and a high-frequency oscillator inductively connected to the quartz wafer, and the quartz wafer is modified with the ammonia-sensitive material. When the ammonia-sensitive material adsorbs ammonia, the surface mass of the quartz crystal changes. The quartz crystal microbalance utilizes the piezoelectric effect of the quartz crystal to convert the surface mass change of the quartz crystal electrode into the frequency change of the electrical signal output by the quartz crystal oscillation circuit, thereby realizing the detection of ammonia.

[0022] Beneficial effects of the present invention:

[0023] The ammonia sensitive material of the present invention has extremely high sensitivity to ammonia. The ammonia sensor made from the ammonia sensitive material of the present invention has high sensitivity, high selectivity and rapid response to ammonia, and has excellent repetitive stability. Ammonia sensitive materials modified with different transition metals show different detection performances under the same test conditions, indicating that different metal centers in the materials have different binding characteristics to ammonia molecules. Among them, the ammonia sensor modified with Co-TPCOF nanosheets shows the highest response to NH3 sensing.

[0024] (155Hz), the fastest response / recovery time (61s / 90s), ultra-high selectivity and excellent reusability provide new materials for the design of high-performance NH3 sensors in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein

[0026] Figure 1 are SEM images of H2-TPCOF (left) and Co-TPCOF (right);

[0027] Figure 2The nitrogen adsorption-desorption curve (left) and pore size distribution diagram (right) of the ammonia-sensitive material;

[0028] Figure 3 is the response value of the ammonia detection device to 100ppm NH3;

[0029] Figure 4 The response / recovery curves of Co-TPCOF (a), H2-TPCOF (b), Ni-TPCOF (c), Cu-TPCOF (d) and Ag-TPCOF (e) ammonia detection devices to 100ppm NH3; the response time comparison of different ammonia detection devices to 100ppm NH3 (f);

[0030] Figure 5 It is the curve of the response value of the Co-TPCOF ammonia detection device changing with the NH3 concentration;

[0031] Figure 6 This is the repeatability test curve of the Co-TPCOF ammonia detection device for 100ppm NH3;

[0032] Figure 7 It is the selectivity of Co-TPCOF ammonia detection device to different gases at 100ppm;

[0033] Figure 8 This is the synthesis route diagram of ammonia-sensitive materials. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0035] Example 1: H2-TPCOF Synthesis

[0036] 5,10,15,20-Tetrakis(4-aminophenyl)porphyrin (TAPP, 27.1 mg, 0.04 mmol) and pyridine-2,6-dicarboxaldehyde (10.8 mg, 0.08 mmol) were added to a mixed solution of ethanol (0.1 mL), 1,2-dichlorobenzene (0.9 mL) and acetic acid (6 M, 0.3 mL), and transferred to a Pyrex tube after ultrasonication for 25 min. The test tube was immediately frozen in 77 K (liquid N2 bath) and degassed to an internal pressure of -100 mTorr. After the temperature returned to room temperature, the Pyrex tube was heated at 120 ° C for 5 d. After cooling to room temperature, the sample was filtered and transferred to a Soxhlet extractor and washed with tetrahydrofuran for 24 h. Finally, vacuum evacuation was performed at 120 ° C for 24 h to obtain an activated sample H2-TPCOF ammonia-sensitive material.

[0037] Example 2: Synthesis of Co-TPCOF

[0038] 330 mg of cobalt acetate was added to a 250 mL glass bottle, 100 mL of ethanol solution was added to the bottle to dissolve, and then 110 mg of activated H2-TPCOF was added, ultrasonicated for 2 min to disperse it, protected by inert gas Ar, and stirred at 45 ° C for 24 h. After the reaction, the product was filtered and thoroughly washed three times with water, methanol and acetone respectively, and the solid product was dried in a vacuum oven for 12 h to obtain the Co-TPCOF ammonia-sensitive material derivative.

[0039] Example 3: Cu-TPCOF Synthesis

[0040] 330 mg of copper acetate was added to a 250 mL glass bottle, 100 mL of ethanol solution was added to the bottle to dissolve, and then 110 mg of activated H2-TPCOF was added, and ultrasonic dispersion was performed for 2 min, and the reaction was stirred at 45 ° C for 24 h under protection of inert gas Ar. After the reaction, the product was filtered and thoroughly washed three times with water, methanol and acetone, respectively, and the solid product was dried in a vacuum oven for 12 h to obtain the Cu-TPCOF ammonia-sensitive material derivative.

[0041] Example 4: Ni-TPCOF Synthesis

[0042] 330 mg of nickel acetate was added to a 250 mL glass bottle, 100 mL of ethanol solution was added to the bottle to dissolve, and then 110 mg of activated H2-TPCOF was added, and ultrasonic dispersion was performed for 2 min, and the reaction was stirred at 45 ° C for 24 h under protection of inert gas Ar. After the reaction, the product was filtered and thoroughly washed three times with water, methanol and acetone, respectively, and the solid product was dried in a vacuum oven for 12 h to obtain the Ni-TPCOF ammonia-sensitive material derivative.

[0043] Example 5: Ag-TPCOF Synthesis

[0044] 330 mg of silver acetate was added to a 250 mL glass bottle, 100 mL of ethanol solution was added to the bottle to dissolve, and then 110 mg of activated H2-TPCOF was added, and ultrasonic dispersion was performed for 2 min, and the reaction was stirred at 45 ° C for 24 h under protection of inert gas Ar. After the reaction, the product was filtered, and washed thoroughly three times with water, methanol and acetone respectively, and the solid product was dried in a vacuum oven for 12 h to obtain the Ag-TPCOF ammonia-sensitive material derivative.

[0045] Example 6: Preparation and detection of ammonia detection device

[0046] The sensitive film material on the surface of the quartz wafer is used to capture the gas to be tested. Based on the sensitivity of the electric quartz wafer to mass, the mass-frequency change relationship of the quartz crystal is used to convert the ammonia concentration signal into a frequency signal output. Based on this principle, the ammonia detection device of this embodiment is prepared. The quartz crystal microbalance (QCM) substrate is cleaned with ethanol and deionized water. The cleaned substrate is fixed on a horizontal plane. The porphyrin-based COF nanosheet material is dispersed in methanol to prepare a solution with a concentration of 1 mg / mL. Then, 3.5 μL of the solution is dripped on the center of the QCM substrate, and the prepared QCM sensor is dried at room temperature for 2 hours.

[0047] (1) Morphological characterization of ammonia-sensitive materials

[0048] Taking H2-TPCOF and Co-TPCOF as examples, the morphology of the ammonia-sensitive materials was characterized by SEM. Figure 1 Both of them have a sheet network structure, and the structure of the ammonia-sensitive material is not changed after post-metallization.

[0049] (2) Specific surface area of ​​ammonia-sensitive materials

[0050] like Figure 2 As shown, nitrogen adsorption-desorption test was performed on the ammonia sensitive material. Figure 2 It can be seen that the specific surface areas of H2-TPCOF, Ni-TPCOF, Co-TPCOF, Cu-TPCOF and Ag-TPCOF decrease in sequence, which are 871.7 m 2 / g, 809.5m 2 / g, 682.0m 2 / g, 510.1m 2 / g and 424.2m 2 / g, this is because the introduction of metal ions significantly reduces the specific surface area of ​​the material, but the pore size of the material does not change significantly.

[0051] (3) NH3 detection performance of ammonia detection device modified with ammonia-sensitive materials

[0052] The ammonia detection device modified with ammonia sensitive materials was compared with the NH3 detection performance. Figure 3As shown. At room temperature and 60% RH, the response of the Co-TPCOF modified ammonia detection device to 100ppm NH3 is about 155Hz, with the best detection performance. Since there is basically no obvious difference in the pore size of several COF materials, but the specific surface area is quite different, generally speaking, the larger the specific surface area of ​​the material, the more sites for NH3 adsorption, but the response value of the material does not change with the change of specific surface area. On the contrary, although the specific surface area of ​​the metallized COF material is reduced, the response to NH3 is greater, which means that the metal center promotes the rapid contact and adsorption of NH3, thereby obtaining excellent sensing performance.

[0053] (4) Response time of the ammonia detection device modified with ammonia-sensitive materials to 100 ppm NH3 The response time of the ammonia detection device modified with ammonia-sensitive materials to 100 ppm NH3 is shown in the figure. Figure 4 The response and recovery time of Co-TPCOF ammonia-sensitive material to 100ppm NH3 are 61s and 90s, respectively, which are significantly faster than other materials, and the slowest one is Ag-TPCOF sensor.

[0054] (5) Effect of NH3 concentration on the response value of Co-TPCOF ammonia detection device

[0055] Figure 5 The linear fitting curve of the response value and concentration of the Co-TPCOF ammonia detection device in the range of 10-300ppm NH3 concentration. The frequency and concentration of the ammonia detection device can be fitted by the equation y=0.29x-125.33. The linear correlation coefficient R 2 =0.97, indicating that the Co-TPCOF ammonia detection device has good linearity.

[0056] (6) Repeatability of NH3 detection by Co-TPCOF ammonia detection device

[0057] According to the previous NH3 performance test results, the Co-TPCOF modified ammonia detection device has the advantages of large response value and fast response to NH3, and is most likely to be used in practical application scenarios. However, the ammonia detection device needs to maintain long-term stability during use, so further testing of the Co-TPCOF modified ammonia detection device for NH3 detection repeatability is required. Figure 6 As shown, the ammonia detection device has good response and recovery characteristics to 100 ppm NH3 after 17 cycles.

[0058] (7) Selectivity of Co-TPCOF ammonia detection device for NH3 detection

[0059] Figure 7The response values ​​of the Co-TPCOF ammonia detection device in different interfering gases at 100 ppm are shown. The detected gases are ammonia, trimethylamine, formaldehyde, toluene, and hydrogen sulfide. The results show that the response value of the Co-TPCOF ammonia detection device to ammonia is significantly higher than that of other gases, indicating that the ammonia detection device has good selectivity and anti-interference ability.

[0060] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. An ammonia-sensitive material based on a covalent organic framework, characterized in that: The ammonia-sensitive material has the following general structural formula: Wherein M is hydrogen or a transition metal element.

2. The ammonia-sensitive material according to claim 1, characterized in that The transition metal element is selected from one or more of cobalt, copper, nickel and silver.

3. A method for preparing an ammonia-sensitive material wherein M is hydrogen in claim 1, characterized in that: The porphyrin derivative is reacted with pyridine-2,6-dicarboxaldehyde in the presence of an organic solvent to prepare the ammonia-sensitive material in which M is hydrogen.

4. A method for preparing an ammonia-sensitive material wherein M is a transition metal element in claim 1 or 2, characterized in that: The following steps are involved: S1, reacting a porphyrin derivative with pyridine-2,6-dicarbaldehyde in the presence of an organic solvent to prepare an ammonia-sensitive material in which M is hydrogen; S2. Mixing an acetate solution containing a transition metal element with the ammonia-sensitive material in which M is hydrogen to obtain the ammonia-sensitive material in which M is a transition metal element.

5. The preparation method according to any one of claims 3 or 4, characterized in that: The porphyrin derivatives include 5,10,15,20-tetrakis(4-aminophenyl)porphyrin.

6. The preparation method according to any one of claims 3 or 4, characterized in that: The organic solvent is a mixed solution of a solvent and a catalyst.

7. The preparation method according to claim 6, characterized in that: The solvent is selected from one or more of ethanol, o-dichlorobenzene, butanol, toluene and dioxane; the catalyst is selected from one or more of acetic acid and scandium trifluoromethanesulfonate.

8. The preparation method according to claim 4, characterized in that: The reaction in step S2 is carried out under an inert atmosphere, at a reaction temperature of 30-60° C., and for a reaction time of 12-36 hours.

9. An ammonia detection device, characterized in that: The invention comprises the ammonia-sensitive material described in any one of claims 1 to 2 or the ammonia-sensitive material prepared by the preparation method described in any one of claims 3 to 8.

10. The ammonia detection device according to claim 9, characterized in that: The ammonia detection device is realized by a quartz crystal microbalance, which includes a quartz wafer and a high-frequency oscillator inductively connected to the quartz wafer, and the ammonia-sensitive material is modified on the quartz wafer.

Citation Information

Patent Citations

  • Imino covalent organic framework polymer and preparation method and application thereof, ammonia gas sensor and preparation method thereof, and ammonia gas sensing detection method

    CN113045722A

  • Covalent organic framework material based on metalloporphyrin as well as preparation method and application of covalent organic framework material

    CN113563551A

  • Preparation of porphyrin-based covalent organic framework material and application of porphyrin-based covalent organic framework material in photocatalysis

    CN116333243A

  • Bifunctional porphyrinyl covalent organic framework material as well as preparation method and application thereof

    CN117143304A

  • Preparation method of electrochemical biosensor and application of electrochemical biosensor in dopamine detection

    CN118566311A